Identification of Candidate Genes for Calcium and Magnesium Accumulation in Brassica napus L. by Association Genetics - Alcock, Thomas D.; Havlickova, Lenka; He, Zhesi; Bancroft, Ian; White, Philip J.; Broadley, Martin R.; Graham, Neil S. (Frontiers in Plant Science, 2017)
Calcium (Ca) and magnesium (Mg) are essential plant nutrients and vital for human and animal nutrition. Biofortification of crops has previously been suggested to alleviate widespread human Ca and Mg deficiencies. In this study, new candidate genes influencing the leaf accumulation of Ca and Mg were identified in young Brassica napus plants using associative transcriptomics of ionomics datasets. A total of 247 and 166 SNP markers were associated with leaf Ca and Mg concentration, respectively, after false discovery rate correction and removal of SNPs with low second allele frequency. Gene expression markers at similar positions were also associated with leaf Ca and Mg concentration, including loci on chromosomes A10 and C2, within which lie previously identified transporter genes ACA8 and MGT7. Further candidate genes were selected from seven loci and the mineral composition of whole Arabidopsis thaliana shoots were characterised from lines mutated in orthologous genes. Four and two mutant lines had reduced shoot Ca and Mg concentration, respectively, compared to wild type plants. Three of these mutations were found to have tissue specific effects; notably reduced silique Ca in all three such mutant lines. This knowledge could be applied in targeted breeding, with the possibility of increasing Ca and Mg in plant tissue for improving human and livestock nutrition.